2021
DOI: 10.1177/17539447211002687
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of infective endocarditis before versus after change of international guidelines: a systematic review

Abstract: Introduction: All major international guidelines for the management of infective endocarditis (IE) have undergone major revisions, recommending antibiotic prophylaxis (AP) restriction to high-risk patients or foregoing AP completely. We performed a systematic review to investigate the effect of these guideline changes on the global incidence of IE. Methods: Electronic database searches were performed using Ovid Medline, EMBASE and Web of Science. Studies were included if they compared the incidence of IE prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 50 publications
0
17
0
3
Order By: Relevance
“…Williams et al recently published a systematic review detailing contemporary epidemiological changes in IE following major guideline changes. 30 They included studies from North America and Europe and concluded that although there was no appreciable increase in IE incidence in North America following pertinent guideline changes, there was a potential rise in incidence in Europe. They included just five European studies in their review, whereas our current investigation includes 18 studies, where the incidence trends were examined statistically over 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al recently published a systematic review detailing contemporary epidemiological changes in IE following major guideline changes. 30 They included studies from North America and Europe and concluded that although there was no appreciable increase in IE incidence in North America following pertinent guideline changes, there was a potential rise in incidence in Europe. They included just five European studies in their review, whereas our current investigation includes 18 studies, where the incidence trends were examined statistically over 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the decline of rheumatic heart disease, a formerly widespread predisposing condition [ 23 ], the incidence appears to be increasing, especially at the expense of the elderly [ 24 ]. There is debate about the last restriction for antibiotic prophylaxis in international guidelines in this trend [ 25 , 26 ]. Still, other epidemiological changes from the last decades with enough influence need to be addressed [ 1 , 24 , 27 ].…”
Section: Epidemiology: a Growing Problemmentioning
confidence: 99%
“… 3 IE is a life-threatening disease with high mortality rates of 14–22% in-hospital and reaching 51% at 10 years despite advances in medical and surgical care. 4 The prognosis for patients with IE is strongly dependent on early diagnosis and prompt treatment. However, the clinical presentation of IE can be highly variable and nonspecific, which potentially leads to a significant delay in diagnosis, thus negatively affecting patient prognosis.…”
Section: Introductionmentioning
confidence: 99%